One-step Cre-loxP organism creation by TAx9 - Martin Miguel Casco-Robles; Tomoki Echigoya; Takeaki Shimazaki; Yuri Murakami; Masaya Hirano; Fumiaki Maruo; Seiya Mizuno; Satoru Takahashi; Chikafumi Chiba (Communications Biology)
Abstract The creation of organisms with Cre-loxP conditional gene recombination systems often faces challenges, particularly when creating the initial (F0) generation with both a Cre recombinase and a DNA site flanked by loxP elements (floxed site). The primary reason is that it is difficult to synthesize a single plasmid with both the Cre gene and the floxed site, since Cre-mediated recombination spontaneously occurs when the plasmid is amplified in Escherichia coli bacterial cells. Here, we introduce an artificial nucleic acid sequence TATATATATATATATATA, named TAx9, that enables the integration of both the Cre gene and the floxed site into a single plasmid. TAx9 effectively blocks spontaneous Cre-mediated recombination in E. coli cells. Using this system, we created an F0 generation of transgenic newts and CRISPR-Cas9 knock-in mice with tissue-specific Cre recombination triggered by tamoxifen. TAx9 technology will be a powerful strategy for creating organisms capable of conditional genetic modification in the F0 generation, accelerating various life science research by reducing the time and cost for ultimately establishing and maintaining lines of genetically modified organisms.